AN ANALYSIS OF SEXISM IN ONLINE MEDIA JPNN.COM AND TRIBUNNEWS.COM NEWS HEADLINES - Ulya Khusnul Khatimah Usman; Jenie Posumah; Agustine Clara Mamentu (Program Studi Pendidikan Bahasa Inggris, 2023)
This study aimed to analyze how sexism are expressed in JPNN.com and TribunNews.com online news headlines. This research used qualitative research, where instead of using numbers, the data collected were words and quotes. In addition, the researcher used stylistic feminist discourse analysis by Sara Mills to analyze sexism in women-related headlines on JPNN.com and TribunNews.com online media. From this study, it could be concluded that there were three forms of sexism that discriminate against female characters in JPNN.com and TribunNews.com news headlines. The three forms of sexism were women as perpetrators of immoral acts, women as objects, and women as inferior. Realizing the shortcomings in this study, the researcher hoped that further research that has the same object of study can be better. Also hopefully that attitudes that refer to sexism in journalism and society can be eliminated.